Literacy of student numeration in solving problems hots based given thinking style - Hasanah, Siti Nur; Utomo, Dwi Priyo; Sutawidjaja, Akbar; Dhakal, Amrit (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Background: Understanding the relationship between students' thinking styles and their numeracy literacy, especially in solving Higher Order Thinking Skills (HOTS) questions, is essential in educational research.Aim: This study aims to explore how students' thinking styles influence their numeracy literacy in addressing HOTS-based questions.Method: A descriptive qualitative approach was employed in this research. The study involved eight students from Larangan 1 Public Middle School, selected through a thinking style questionnaire. Two students were chosen from each of the four identified thinking style categories. Data were collected using tests comprising two HOTS-based questions and interviews.Results: The findings indicate that students' numeracy literacy varies significantly according to their thinking styles when solving HOTS questions. Students identified as SK and SA exhibited higher numeracy literacy, effectively utilizing various symbols and numbers, analyzing tabular information, and interpreting these analyses to make decisions. In contrast, students labeled as RK were only able to fulfill two numeracy literacy indicators and struggled with information analysis. RA students faced challenges in correctly writing numbers or symbols, analyzing information, and articulating problem-solving processes and conclusions. The study also found that students who process information sequentially exhibited better numeracy literacy in solving HOTS-based questions.Conclusion: The study concludes that students' thinking styles play a crucial role in their numeracy literacy, particularly in solving HOTS-based mathematical problems. This insight underscores the importance of considering individual cognitive styles in educational strategies to enhance mathematical problem-solving skills.